Extensive validation study of the Parkinson's Disease Composite Scale. (31st May 2019) - Martinez‐Martin, P.; Radicati, F. G.; Rodriguez Blazquez, C.; Wetmore, J.; Kovacs, N.; Ray Chaudhuri, K.; Stocchi, F.; ,
Abstract : Background and purpose: A composite instrument able to rapidly and reliably assess the most relevant motor and non‐motor afflictions suffered by Parkinson's disease (PD) patients in a real world clinic setting is an unmet need. The recently validated PD Composite Scale (PDCS) was designed to fulfil this gap as a quick, comprehensive PD assessment. The objective of this study was extensive evaluation of the PDCS's clinimetric properties using a large international sample. Methods: This was a cross‐sectional study in which the PDCS, the Movement Disorder Society Unified Parkinson's Disease Rating Scale and the Clinical Impression of Severity Index for PD were applied. Basic clinimetric attributes of the PDCS were analysed. Results: In total, 776 PD patients were included. The PDCS total score showed negligible floor and ceiling effects. Three factors (54.5% of the variance) were identified: factor 1 included motor impairment, fluctuations and disability; factor 2, non‐motor symptoms; and factor 3, tremor and complications of therapy. Cronbach's alpha was from 0.66 to 0.79. Inter‐rater reliability showed weighted kappa values from 0.79 to 0.98 for items and intraclass correlation coefficient values from 0.95 (Disability) to 0.99 (Motor and total score). The Bland–Altmann method, however, showed irregular concordance. PDCS standard error of measurement and convergent validity with equivalent constructs of other measures were satisfactory (≥0.70). PDCS scores significantly differed by Hoehn and Yahr stage. Conclusion: Overall, in line with previous findings, the PDCS is a feasible, acceptable, valid, reliable and precise instrument for quickly and comprehensively assessing PD patients.